Hellprint Bandung dalam Ekosistem Industri Musik Indonesia: Manajemen Acara Musik Metal sebagai Bagian dari Ekonomi Kreatif - Diputra, Agus Sukarna; Reffali, Soni (Jurnal Sekretaris dan Administrasi Bisnis, 2026)
Based on its headquarters in Bandung, Hellprint is one of the largest metal music event organizers (EO) in Indonesia. This study aims to examine Hellprint's business management, its position in the national music industry, and its contribution to the creative economy. Data were collected through secondary documentation analysis, literature review, and digital media observation relevant to Hellprint activities. The results show that Hellprint has developed a community-based business model through revenue diversification strategies, including ticket sales, merchandising, and sponsorship. This strategy strengthens business sustainability and contributes to Bandung's creative economy through the growth of supporting industries and job creation. This study concludes that creative, adaptive, and community-oriented management is a key factor in sustaining extreme music events in Indonesia